The contribution of fibrinogen to inflammation and neuronal density in human traumatic brain injury - Jenkins, D; Craner, M; Esiri, M; De Luca, G (Mary Ann Liebert Inc, 2018)
Traumatic brain injury is a leading cause of death and disability, particularly among the young. Despite this, no disease-specific treatments exist. Recently, descriptions of BBB disruption and parenchymal fibrinogen deposition have been reported in acute traumatic brain injury and in long-term survival; however, their contribution to the neuropathology of TBI remains unknown. 1, 2 The presence of fibrinogen - a well-documented activator of microglia/macrophages - may be associated with neuroinflammation, and neuronal/axonal injury. To test this hypothesis, cases of human TBI with survival times ranging from 12 hours to 13 years (survival <2months n = 15, survival >1year n = 6) were compared with uninjured controls (n = 15). Tissue was selected from the frontal lobe, temporal lobe, corpus callosum, cingulate gyrus and brainstem, and the extent of plasma protein (fibrinogen and IgG) deposition, microglial/macrophage activation (CD68 and Iba-1 immunoreactivity), neuronal density, and axonal transport impairment (APP immunoreactivity) were assessed. Quantitative analysis revealed a significant increase in parenchymal fibrinogen and IgG deposition following acute TBI compared with long-term survival and control. Fibrinogen, but not IgG, was associated with microglial/macrophage activation and a significant reduction in neuronal density. Perivascular fibrinogen deposition was also associated with microglial/macrophage clustering and accrual of APP in axonal spheroids, albeit rarely. These findings mandate the future exploration of causal relationships between fibrinogen deposition, microglia/macrophage activation and potential neuronal loss in acute TBI .